Pengaruh Mata Kuliah Manajemen Kewirausahaan terhadap Minat Berwirausaha Mahasiswa (Studi di Program Studi Administrasi Pendidikan Universitas Puangrimaggalatung) - Erviana Abdullah; Sumarni Sumarni; Besse Herlina; Nurfadillah Nurfadillah (Journal of Education and Teaching (JET), 2021)
This research is motivated by the lack of interest in entrepreneurship by students of the Education Administration Study Program. Therefore, this study aims to determine the effect of entrepreneurship courses on the entrepreneurial interest of students of the Education Administration Study Program, FKIP University of Puangrimaggalatung. This type of research is quantitative research with data collection using surveys and analytical documents. The population in this study were students of the Puangrimaggalatung University Education Administration Study Program class of 2019, totaling 34 students. The data analysis technique used percentage analysis, simple regression test, and t test. The results of this study indicate that the entrepreneurial management course has a positive and significant influence on the entrepreneurship interest of the students of the Educational Administration Study Program, FKIP Puangrimaggalatung University.